Pendampingan Manajemen Produksi Pertunjukan Pada Kegiatan Barakan Pelestari Seni Budaya Nusantara - Pramono, Koko Hari; Sugmatimur, Yuddan Fijar (Gayatri : Jurnal Pengabdian Seni dan Budaya, 2024)
Mentoring activities in community organisation groups community, namely Pelestari Seni Budaya Nusantara or abbreviated as PASEBAN, is an activity to support community participation in efforts to preserve traditional arts. preservation of traditional arts. Pelestari Seni Budaya Nusantara is a cultural arts development institution with a pesantren background. cultural arts development institution that has a pesantren background, this is a commitment of the group. This is a commitment of the art preservation group to be directly involved in art activities that are held regularly. directly in art activities that are held regularly. One of the activity programmes in Pelestari Seni Budaya Nusantara is Barakan. Barakan is one of the activities carried out during the commemoration of the maulud of the great prophet Muhammad SAW. This activity is a routine activity held every year by the Babul Khoir Islamic Boarding School. by Babul Khoir Islamic boarding school. The caregiver of this boarding school is named Khirul Al Hanafi or more familiarly addressed as Gus Rul is one of the initiators of the Barakan idea. one of the initiators of the idea of Barakan, the selection of the name barakan is one of the activities that make tumpeng with arranged in the form of activities that make tumpeng arranged in the shape of a mountain and then will be contested by the surrounding community. contested by the surrounding community, then in addition there are also held social service activities and with bantengan art entertainment as a complement. Translated with DeepL.com (free version)